Conceptions of disability by college students in two politically different countries: Cuba and Brazil - Leite, Lúcia Pereira; Oliveira, Taize de; Serrano, Elsie Alejandrina Perez (Faculdade de Filosofia e Ciências, 2018)
Dealing with the disability is linked to ideological specifications, signified by the society. In this way, analyzing the manner how distinct political-economical contexts, Cuba and Brazil, position concerning this issue is the core of this study. The first, represented by a socialist republic with an inner organization centered in the Marxist-Leninist and communist model, whereas the latter is featured by the capitalist model, in a productivity-focused perspective. Objective of this research is to identify the concepts of disability in both countries and investigate the conceptions of disability, using the Disability Conception Scale (DCS) in two groups of college students, comparing the discoveries. 272 Cuban students and 344 Brazilian ones participated in this study. Analysis identified similar descriptive data between the samples. Through median analysis, it is highlighted that, in Brazil, there are a tendency to agree with utterances related to a historical-cultural interpretation of disability, followed by a social interpretation. In Cuba, the tendency was an agreement with utterances which conceive disability as a social phenomenon, followed by the biological and historical-cultural interpretations. Both contexts indicated low agreement with utterances which conceive the disability as a metaphysical phenomenon. Highlighting conceptions of college students about disability is interesting because it brings to the scientific debate how forthcoming professionals position themselves in face of this social group and can indicate how universities have worked issues related of this group.